Association of mitochondrial iron deficiency and dysfunction with idiopathic restless legs syndrome. Issue 1 (11th October 2018) - Haschka, David; Volani, Chiara; Stefani, Ambra; Tymoszuk, Piotr; Mitterling, Thomas; Holzknecht, Evi; Heidbreder, Anna; Coassin, Stefan; Sumbalova, Zuzana; Seifert, Markus; Dichtl, Stefanie; Theurl, Igor; et al.
ABSTRACT: Background: Restless legs syndrome is a sensorimotor neurological disorder of the limbs that impairs quality of life and disturbs sleep. However, there has been progress in understanding the disease involving the dopaminergic system as well as iron metabolism. The exact pathophysiological mechanisms of restless legs syndrome remain elusive. We tried to elucidate the underlying mechanisms in iron metabolism in restless legs syndrome subjects on a systemic, cellular, and mitochondrial level. Methods: We conducted a study prospectively recruiting 168 restless legs syndrome patients and 119 age‐matched healthy controls focusing on iron metabolism using human monocytes as surrogates. Results: Evaluation of systemic iron metabolism parameters in the circulation showed no significant difference between patients and controls. We observed a significant reduction in mRNA levels of heme oxygenase 1 and mitochondrial iron genes like mitoferrin 1 and 2 in monocytes isolated from restless legs syndrome patients, indicating mitochondrial iron deficiency. Interestingly, we also observed reduced expression of iron regulatory protein 2 along with impaired activity of mitochondrial aconitase and reduced mitochondrial superoxide formation in restless legs syndrome subjects. Along this line, patients had reduced mitochondrial respiratory capacity that improved in restless legs syndrome subjects under treatment with dopaminergic drugs compared with untreated patients. Conclusions: Our data suggest that restless legs syndrome is linked to mitochondrial iron deficiency and associated impairment of mitochondrial function. This is partly corrected by treatment with dopaminergic drugs compared with untreated patients, which may be linked to an effect of dopamine on cellular iron homeostasis. © 2018 International Parkinson and Movement Disorder Society